Myocardial contractile dysfunction contributes to the development of heart failure in rats with aortic stenosis - Bregagnollo, Edson A.; Zornoff, Leonardo Antonio Mamede [UNESP]; Okoshi, Katashi [UNESP]; Sugizaki, Mario; Mestrinel, Marco A.; Padovani, Carlos Roberto [UNESP]; Cicogna, Antonio Carlos [UNESP] (Elsevier B.V., 2007)
Objectives: To analyze the potential contribution of contractility state and ventricular geometry to the development of heart failure in rats with aortic stenosis.Methods: Rats were divided into three groups: compensated aortic stenosis (AS, n = 11), heart failure AS (n = 12) and control rats (C, n = 13).Results: After 21 weeks, failing AS rats presented higher systolic (C = 36.6 +/- 3.1, AS-78.6 +/- 4.8*, failing AS = 104.6 +/- 7.8*) and diastolic meridian stress (C = 6.9 +/- 0.4, AS = 20.1 +/- 1.1*, failing AS = 43.2 +/- 3.2*(dagger)), hydroxyproline (C = 3.6 +/- 0.7 mg/g, AS = 6.6 +/- 0.6* mg/g, failing AS = 9.2 +/- 1.4*(dagger) mg/g) and cross-sectional area (C = 338 +/- 25 mu m(2), AS = 451 +/- 32* mu m(2), failing AS = 508 +/- 36*(dagger) mu m(2)), in comparison with control and compensated AS animals (*p < 0.05 vs. control, (dagger)p < 0.05 vs. AS). In the isometric contraction study, considering the time from peak tension to 50% relaxation (RT50), the relative variation responses, following post-rest contraction and increase in Ca2+ concentration, were higher in failing AS than compensated AS animals. In contrast, following post-rest contraction, compensated AS group presented higher values of the peak developed tension (DT) than failing AS group. Following beta-adrenergic stimulation, control animals presented higher values of +dT/dt and -dT/dt than AS animals. In addition, failing AS animals presented higher TPT values than compensated AS animals.Conclusion: Myocardial contractile dysfunction contributes to the development of heart failure in rats with aortic stenosis. (c) 2006 Elsevier B.V.. All rights reserved.
Keywords: cardiac dysfunction; fibrosis; hypertrophy; pressure overload; ventricular remodeling